Eichmann before Jerusalem : the unexamined life of a mass murderer - Stangneth, Bettina (Alfred A. Knopf, 2014)
"A total re-assessment of the life of Adolf Eichmann that reveals his activities and notoriety amongst a global network of National Socialists following the collapse of the Third Reich, and permanently undermines Hannah Arendt's often-cited notion of the "banality of evil.""--